Managing and Leading Nonprofit Organizations : a framework for success - Dann, Paul L. (Hoboken, New Jersey : Wiley, 2022)
"Leading and Managing Nonprofit Organizations will provide leaders and managers with practical strategies for ensuring organizational success. Dann's 30+ years of experience developing and advancing organizational success is brought to bear to enable the reader to advance their own practice-based leadership capabilities. The book is filled with practical strategies to assure successful leadership practice with universally applicable examples of how identified strategies are implemented and leadership tools that can be successfully applied in practice. Seasoned as well as newly minted leaders will experience this book as an indispensable tool for advancing their leadership practice. Leaders across various sectors, from the nonprofit and public sector, will benefit from the balance of theory and practice. In light of growing complexity and increasing challenges, today's organizations require leadership practice that is highly adaptive, flexible, and effective. Leading and Managing Nonprofit Organizations provides readers with the capacity to develop and refine their ability to meet the leadership demands of today's organizations"--
Includes bibliographical references and index.
Keywords: Nonprofit organizations -- Management; Leadership